Characterization of the Gut Microbiota of the Antarctic Heart Urchin (Spatangoida) Abatus agassizii - Schwob, Guillaume; Cabrol, Léa; Poulin, Elie; Orlando, Julieta (Frontiers in Microbiology, 2020)
Abatus agassizii is an irregular sea urchin species that inhabits shallow waters of South Georgia and South Shetlands Islands. As a deposit-feeder, A. agassizii nutrition relies on the ingestion of the surrounding sediment in which it lives barely burrowed. Despite the low complexity of its feeding habit, it harbours a long and twice-looped digestive tract suggesting that it may host a complex bacterial community. Here we characterised the gut microbiota of specimens from two A. agassizii populations at the south of the King George Island in the West Antarctic Peninsula. Using an amplicon sequencing approach targeting the 16S rRNA gene, the goals of this study were to explore the Abatus microbiota composition and putative functional capacity, evaluating its differentiation among the gut content and the gut tissue in comparison with the external sediment. Additionally, we aimed to define a core gut microbiota between A. agassizii populations to identify potential keystone bacterial taxa. Lastly, we examined the keystone taxa micro-diversity looking for sample types’ specialisation pattern at the oligotype scale. Our results show that the diversity and the composition of the microbiota, at both genetic and predicted functional levels, were mostly driven by the sample type, and in a lesser extent by the population location. Differential enrichment in specific bacterial taxa, belonging mostly to Planctomycetacia and Spirochaetia, was observed in the gut content and the gut tissue respectively. Predictive functional profiles revealed higher abundance of specific pathways, as the sulfur cycle in the gut content and the amino acid metabolism, in the gut tissue. Further, the definition of a core microbiota allowed to obtain evidence of specific localization of bacterial taxa at a high taxonomic resolution (>97% sequence similarity of the 16S rRNA gene) and the identification of potential keystone taxa assigned to the Desulfobacula and Spirochaeta genera as potentially host selected. The ecological relevance of these keystone taxa in the host metabolism is discussed.